Better performance pulsed launcher system by adjusting projectile initial position - Mohamed, Mohd Rezal; Iqbal, Syed Javaid; Hon, Kah Wye (IEEE, 2008)
A Pulsed Launcher System is developed using a electromagnetic induction technology. The launcher consists of coil, capacitor banks, and projectile is optimized by focusing on the projectile initial position inside the coil. The position of projectile is adjusted and projectile is launched with a different setting of capacitor banks and projectile’s highest speed is obtained.